Clinical Profile, Echo, and Outcome of Congenital Heart Disease in First Two Years of Life - Khattak, Noor Ul Haram; Khaliq, Abdul; Khattak, Noor Ul Saba; Gul, Haji (Biological and Clinical Sciences Research Journal, 2025)
Due to the lack of high-quality echocardiography in developing countries mostly neonates with CHD die each year. Objective: The aim of the study was to find out the Clinical profile, echo, and outcome of congenital heart disease in first two years of life. Method: The current study was carried out in neonatal intensive care unit Bacha Khan Medical Complex/Gajju khan Medical college Swabi from July 2023 to December 2023 after taking permission from the ethical board of the institute. A total of 54 children of day zero to two years presented to the NICU with congenital heart diseases were enrolled in this study. Echo-machine was used to perform transthoracic echocardiography (TTE).Throughout the research period, the study population was evaluated in order to determine the outcome of congenital cardiac disease. A pre-tested, semi-structured questionnaire was used to record all pertinent data in a prepared datasheet Microsoft Excel was used to analyze the data, which were then shown as tables and figures. Results: A total of 54 children with congenital heart defect were included in this study. Of these, 38.1% of cases were identified between the ages of 13 - 24 months, while 61% of cases were diagnosed between the ages of 0-12 months. Out of 54 individuals, 15 (27%) had cyanotic heart lesions and 36 (66.6%) had a cyanotic heart lesions. VSD was the most common structural defect, Complaints of children with CHD showed cough in most cases (82%), dyspnea in 80%, poor weight gain in 70%, breathing difficulty in 68% and fever in 58% cases. Among children with congenital heart disease, murmur was the most prevalent presenting symptom (85%). In both age groups, 57.4% of the participants had a history of over two respiratory symptom episodes. Out of the total participants 66% Advice for Surgery or conservative treatment and 9 % of individuals died. Conclusion: This study concluded that echocardiography play a major role in the diagnosis and management of congenital heart disease in first two years of life .the death rate was recorded 9% in this study which further revealed that early management of CHD is crucial.